CERASTIUM MAHMUTKILINCII (CARYOPHYLLACEAE), A NEW SPECIES FROM TÜRKIYE - Keski̇n Mustafa; Karaer, Fergan; Celep, Ferhat (Phytotaxa, 2024)
Cerastium (Caryophyllaceae) is a taxonomically difficult genus of over than 100 species. The flora of Türkiye include 30 species of Cerastium, of which 9 are endemics. A further species (Cerastium mahmutkilincii sp. nov.), belonging to sect. Cerastium subsect. Grandiflora, was proposed here based on a morphological investigation of herbarium specimens. The new species is only known from the Erbaa-Tokat region (North Anatolia) and it is similar to C. szowitsii and C. araraticum, but differs from both by the hairy filaments and sparsely glandular (eglandular hairy in both C. szowitsii and C. araraticum) and multicellular hairy stem indumentum (usually simple hairy in C. szowitsii and C. araraticum). It also differs from C. araraticum by a hairy claw at the base (glabrous in C. araraticum). Data about the ecology and phenology, as well as a identification key of the Turkish members of subsect. Grandiflora are also given; lacking sufficient data, the IUCN conservation status was assessed as DD (Data Deficient). As a result, with the new species in this article, the number of Cerastium species in Türkiye has increased to 31 and the number of endemic taxa to 10.